2010
DOI: 10.1080/13675560903268886
|View full text |Cite
|
Sign up to set email alerts
|

Towards the integrative supply chain model

Abstract: Although empirical studies show that supply chain integration is associated with high levels of business and operational performance, some authors argue that there is no need to pursue total end-to-end supply chain integration and different or relationship-by-relationship approaches are needed. This paper introduces the first step in the development of the business process model, which might facilitate the building of closer relationships among businesses and therefore endorse supply chain integration. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
(94 reference statements)
0
16
0
Order By: Relevance
“…Grubic et al (2010) have mentioned the advantage of the GSCF reference model to the other SC configuration models. Lambert (2008) has introduced the IBMS performance measurement framework to measure the performance of the SCs, which are configured based on the GSCF model.…”
Section: Proving the Plansmentioning
confidence: 99%
See 3 more Smart Citations
“…Grubic et al (2010) have mentioned the advantage of the GSCF reference model to the other SC configuration models. Lambert (2008) has introduced the IBMS performance measurement framework to measure the performance of the SCs, which are configured based on the GSCF model.…”
Section: Proving the Plansmentioning
confidence: 99%
“…It seems that the previous studies generally focus on SCOR-based ontologies. Grubic et al (2010) have suggested the creation of a GSCF-based ontology to define objects classes, the relationships among those classes and the SC dyadic relationships in future researches. As another innovation, this paper provides a GSCF-based ontology, which could be applied to the SCPMS.…”
Section: Ontologymentioning
confidence: 99%
See 2 more Smart Citations
“…As a competitive strategy, supply chain management is widely acknowledged as offering greater competitive advantage for firms than traditional logistics, marketing, and operations strategies (Bowersox et al, 2003;Christopher & Peck, 2004;Cooper et al, 1997;Grubic et al, 2010). Implementing successful supply chain strategies, however, requires the internal integration of functional activities such as logistics, marketing, and operations.…”
mentioning
confidence: 97%